2018
DOI: 10.1002/2211-5463.12421
|View full text |Cite
|
Sign up to set email alerts
|

FGF‐2 suppresses expression of nephronectin via JNK and PI3K pathways

Abstract: Nephronectin (Npnt), an extracellular matrix protein, is a ligand for integrin α8β1 and is involved in the development of various organs, such as the kidneys, bones, liver, and muscles. Previously, we found that Npnt expression was inhibited by various cytokines including transforming growth factor‐β ( Tgf ‐β) and oncostatin M (Osm). Fibroblast growth factor ( Fgf )‐2, otherwise known as basic Fgf, also plays important roles in skeletal development and postnatal os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…More recently, it was reported that Npnt is a potential prognostic marker in breast cancer and that Npnt mediates p38 mitogen-activated protein kinase (MAPK)–induced cell viability [38]. Npnt expression was suppressed by fibroblast growth factor (FGF)-2 via c-Jun N-terminal kinase (JNK) in MAPK and Phosphoinositide 3-kinase (PI3K) pathways [39]. However, no correlations have been reported in the case of lung fibrosis.…”
Section: Silicosis and Integrinmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was reported that Npnt is a potential prognostic marker in breast cancer and that Npnt mediates p38 mitogen-activated protein kinase (MAPK)–induced cell viability [38]. Npnt expression was suppressed by fibroblast growth factor (FGF)-2 via c-Jun N-terminal kinase (JNK) in MAPK and Phosphoinositide 3-kinase (PI3K) pathways [39]. However, no correlations have been reported in the case of lung fibrosis.…”
Section: Silicosis and Integrinmentioning
confidence: 99%
“…However, it has been indicated that profibrotic growth factors such as FGF-2 [39] and TGF-β [69,70] and the profibrotic JAK/STAT pathway [70] suppress the expression of Npnt. These investigations focused on osteogenesis.…”
Section: Npnt In Silicosismentioning
confidence: 99%
“…GROUP 1 PSENEN, CXCR1 [5] GROUP 2 BMP6, SMAD3 [19] BMP6, MAPK1 [96] MAPK1, SMAD3 [26] MAPK1, MAPT [51] MAPK1, PRKCQ [15] GROUP 3 ASXL2, BIRC6 [43] GROUP 4 FGFR1, TGFBR3 [88] FGFR1, NPNT [41] GROUP 5 BMP4, MMP10 [27] BMP4, HSD17B1 [4] 9 Data from https://www.kaggle.com/datasets/raghadalharbi/ breast-cancer-gene-expression-profiles-metabric…”
Section: Group Features Refmentioning
confidence: 99%
“…Tumour necrosis factor α(TNFα) Nuclear factor-κB (NF-κB) [62] Transforming growth factor β(TGF-β) ALK5, Smad2 ERK1/2, JNK, MAPK [23,63,64] Fibroblast growth factor-2 (FGF-2) JNK PI3K [65] Interleukin-1β(IL-1β) JNK ERK1/2 [66] Oncostatin M (OSM) JAK/STAT MAPK [67] Inorganic Phosphate FGFRs (via Pit) [68] Mmu-miRNAs 23a, 101a, 296-5p, 328, 425 GSK3β, Cyclin D, ERK [69] Up-regulation Wnt3a Wnt β-catenin, TCF/LEF [42,70,71] Bone morphogenetic protein-2 (BMP-2) [72] Vitamin D 3 Vitamin D receptor (VDR) [73] Fibroblast growth factor 10 (FGF10) transcription factor T box 5 (Tbx5) [43] Insulin growth factor (IGF) IGFR-ERK1/2 [74] ? ERK5-Sp1-Klf2/4 [75] Most studies on NPNT regulation (Table 1) are done on osteoblasts, where the protein has a central role in differentiation.…”
Section: Down-regulationmentioning
confidence: 99%